The knowledge, attitude and practices of pregnant women in preventing iron deficiency anemia in Georgia - Verulava, Tengiz (One Health & Risk Management, 2025)
Introduction. Anemia in pregnancy is a serious global health challenge, affecting, especially developing countries. Materials and methods. A qualitative research method was used to survey pregnant women with iron deficiency anemia (IDA) and physicians through in-depth interviews. The target sample consisted of 9 gynecologists and 26 pregnant women, selected through purposive sampling from three maternity hospitals in Tbilisi (Georgia). Results. The majority of pregnant women (n=22; 84.6%) knew IDA and correctly identified its symptoms. However, despite high awareness, most lacked adequate knowledge about the causes and risk factors of IDA. While pregnant women were aware of healthy eating practices, they did not follow a proper diet. Relevant obstacles to adopting a healthy eating pattern included limited financial access to food as well as cultural and religious barriers. Although the respondents had some knowledge about iron-rich foods, they were generally unaware of the need to take iron supplements for prevention. The majority of pregnant women (n=21; 80.8%) received little information about anemia from their family physicians, indicating the limited role of family doctors in preventing IDA during pregnancy. Conclusions. Although pregnant women have knowledge and positive attitudes regarding the prevention of IDA, the practice is unsatisfactory. The results indicate a weak link between knowledge about IDA prevention and healthy behavior, which is a major contributing factor to the prevalence of anemia. To solve the problem, it is necessary to encourage proper counseling on nutrition for pregnant women during antenatal care, with a key role played by family doctors. Raising awareness of the problem among women of reproductive age and adolescent girls should also be promoted.